Study of minority carrier injection phenomenon on Schottky and plasma deposited p-n junction diodes - Ozdemir, Orhan; Sel, Kivanc (ELSEVIER SCI LTD, 2009)
Both temperature dependent ac capacitance (C) together with ac conductance (G) under various frequencies (omega) and dc current (I) measurements as functions of bias (V) were employed to investigate majority as well as minority carrier injection phenomenon on chromium-p-type crystalline silicon (Cr/p-cryst. Si/ohmic contact) Schottky and aluminum/plasma deposited n-type hydrogenated amorphous silicon/p-c-Si (Al/n-aSi:H/p-c-Si/ohmic contact) p-n structures. Ambipolar transport process was eventual for both diodes and behaved differently according to the mentioned techniques: for a well defined forward bias interval, there was an increase in capacitance towards maximum that interpreted as majority carrier injection from the back electrode. On the other side, minority carrier injection from front electrode begun when the bias went beyond the critical voltage (i.e., built-in voltage) that corresponded to the peak position and caused sharp decrease in measured capacitance, leading to observation of a hump in C-V measurement. Moreover, shape and peak position of the hump were frequency/temperature dependent. Remarkably, in the bias range where capacitance pronounced, space charge limited current (SCLC) was discerned as enrolled carrier flow mechanism according to I-V measurement, confirming further majority carrier injection. In addition, both dc conductivity and ac conductance followed the same dependence with bias voltage in forward direction. On the other side, reverse current seemed proportional to square root of reverse bias, implying generation current in the depletion region. These experimental identifications convinced us of the existence of conductivity modulation issue for the structures at hand. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Conductivity modulation; Minority carrier injection; INFRARED-ABSORPTION; TRANSPORT; Engineering; Materials Science; Physics